2019
DOI: 10.11648/j.fem.20190502.13
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Some Agro-Wastes for Cultivation of <i>Pluerotus ostreatus</i> (Oyster Mushroom) in Keffi Nigeria

Abstract: Commercial crop production and many other agro-industrial activities generate large amount of cellulose, hemicelluloses and lignin. This research is aimed at the utilization of some of these agro-wastes for the cultivation of Pleurotus ostreatus (Oyster Mushroom) in Keffi area. The agro-wastes (cassava peels (CP), banana leaves (BL), saw dust (SD), yam peels (YP) and groundnut shells (GS) were collected, sorted, shredded, sterilized and inoculated with equal proportions of Pleurotus ostreatus (P. osreatus) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In other worse scenarios, these byproducts that are not properly discarded end up contaminating the water bodies like rivers and lakes. Overall, the environmental impact can be noticed in water, soil, and air quality [34,[37][38][39], and the approach of circular economy management becomes relevant when the data show that, for example, fruit byproducts-such as peels, bagasse, seeds, and stems-represent almost 50% of fresh fruit and have high nutritional value, which is sometimes present even in a higher concentration compared to the final product available, and the cost efficiency of these byproducts is different in different years and countries [38]. By 2017, the circular economy approach differed from these traditional practices in the way that the recovery and valorization of wastes and byproducts became a main objective, with the final purpose to put them back in the supply chain to generate economic growth [40].…”
Section: Oyster Mushroom and Agro-waste Managementmentioning
confidence: 99%
“…In other worse scenarios, these byproducts that are not properly discarded end up contaminating the water bodies like rivers and lakes. Overall, the environmental impact can be noticed in water, soil, and air quality [34,[37][38][39], and the approach of circular economy management becomes relevant when the data show that, for example, fruit byproducts-such as peels, bagasse, seeds, and stems-represent almost 50% of fresh fruit and have high nutritional value, which is sometimes present even in a higher concentration compared to the final product available, and the cost efficiency of these byproducts is different in different years and countries [38]. By 2017, the circular economy approach differed from these traditional practices in the way that the recovery and valorization of wastes and byproducts became a main objective, with the final purpose to put them back in the supply chain to generate economic growth [40].…”
Section: Oyster Mushroom and Agro-waste Managementmentioning
confidence: 99%
“…It was noted that the use of agro-waste as a source of plant nutrients serves as environmental sanitation as well as reduction in craving for mineral fertilizers by farmers. [15,16] reported that the SMC was entangled with innumerable mushroom threads collectively referred to as mycelia which could have modified the substrate biochemically by production of enzymes. Sprouting grains for human consumption has been used for centuries in Asian countries to improve food value [17].…”
Section: Introductionmentioning
confidence: 99%